Management Information System of Event Organizer - Gede Yudiyana, I Made; Sumichan, Andrew; Sri Ariyani, Ni Wayan (International Journal of Engineering and Emerging Technology; Vol 3 No 2 (2018): July - December, 2019)
The rapid development of technology has had a major impact on the development of the industry to simplify the business processes involved. Event Organizer in the field of conference events is one of them which has many activities in one event that can be held more than one day. The management information system will assist and facilitate event activities in terms of ticket sales, booths, accommodation and activities outside of events such as tours held by organizer. The research methodology carried out begins with interviews with business operators organizing the event to look for functional requirements which are then produced at the end of the research a system that is in accordance with the needs to assist ongoing activities.